Answer = 6
Explanation:
I'm guessing there's a simpler solution, but let's give it a shot.
The two roots are provided by using the quadratic equation:
x = [-b ± √(b2 - 4ac)] / (2a)
For x2 - 10x + q = 0
a = 1
b = -10
c = q
Substituting these values in:
x = [-b ± √(b2 - 4ac)] / (2a)
= [-(-10) ± √((-10)2 - 4(1)(q))] / (2(1))
= [10 ± √(100 - 4q)] / 2
= 0.5 [10 ± √(100 - 4q)]
The first root, x1
x1 = 0.5 [10 + √(100 - 4q)]
= 5 + 0.5√(100 - 4q)
The second root, x2
x2 = 0.5 [10 - √(100 - 4q)]
= 5 - 0.5√(100 - 4q)
The difference in the roots is 6.
6 = x1 - x2
= [5 + 0.5√(100 - 4q)] - [5 - 0.5√(100 - 4q)]
= 5 + 0.5√(100 - 4q) - 5 + 0.5√(100 - 4q)
6 = √(100 - 4q)
(6)2 = [√(100 - 4q)]2
36 = 100 - 4q
-64 = -4q
q = 16
Do a little more work to determine the roots.
x2 - 10x + q = 0
x2 - 10x + 16 = 0
(x - 8)(x - 2) = 0
x = {2, 8}
8 - 2 = 6